Effect of organic bio-polymer on bio-mineralization of CaCO3 - Nawarathna, T.H.K.; Nakashima, K.; Kawasaki, S. (My University, 2017)
: Organic matrix in the biogenic CaCO3 has a significant influence on the CaCO3 crystal growth, its polymorphs and morphology. In this research, effect of the cationic and anionic organic bio-polymers on the crystallization of CaCO3 was investigated in microbial induced carbonate precipitation (MICP) process. In the current study, poly-L-lysine and poly-glutamate were used as cationic and anionic biopolymers, respectively. Urea hydrolysis by ureolytic bacteria Pararhodobacter sp. led to CaCO3 formation in the presence of Ca2+ ions. The reaction was conducted with the addition of the polymers under different conditions. After oven-drying precipitation, the amount of precipitate was measured, and morphology of the precipitate was analyzed by using scanning electron microscope. Bell-shaped curve was obtained in the relationship between the amount of the precipitate and the poly-L-lysine concentration. However, amount of precipitate remained approximately constant with the increase of the poly-glutamate concentration. In the presence of poly-L-lysine, morphology of the crystals changed from well-developed rhombohedral crystals to ellipsoidal shaped aggregates. But in poly-glutamate addition, polyhedral and spherical crystals are predominant.
Keywords: Biopolymer; Calcite; Microbial induced carbonate precipitation; Morphology